PREDIKSI LAJU EROSI MENGGUNAKAN METODE USLE DAN SISTEM INFORMASI GEOGRAFIS (SIG) (STUDY KASUS DAS SELANGIS) - Elpita Aisah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Erosion and sidimentation are processes that occur continuously in river flows. The hose watershed is one of the watersheds that often experiences erosion. This is due to land clearing triggered by a rapid increase in population in the selangis watershed. In this study, we used a USLE method based on a geographic information system by calculating erosion rates that consider erosivity factors, erodibility, slope factors and slope lengths, land cover factors and conservation-specific action factors. The rainfall data used in the settlement can be obtained from PTPN 7 Pagar alam. From the results of the calculation, the value of the Elapsivity Index (EI30) was 863,017 N/h. Watershed area (1) 2,583,8625 ha, watershed (2) 6,897.5 ha, watershed (3) 464,375Ha, watershed (4) 666.0625 ha, watershed (5) 2,555 ha, watershed (6) 4,607.0625 ha. And the minimum erosion is 10,775 tons/year, the maximum erosion is 110,360 tons/year,because of the large erosion, sedimentation occurs and conservation is needed to overcome it.'